Story-shaped worship : following patterns from the Bible and history - Castleman, Robbie, 1949- (Downers Grove, Illinois : InterVarsity Press, 2013)
"What is the right way to worship? Right worship does not require a return to the identical forms found in the early church, or later in Rome, or after that in Westminster. What it calls for is a faithful response today to the God of our salvation in light of those biblically ordered and historically informed patterns. In this study Castleman uncovers the fundamental shape of worship. What she unearths is a shape that is outlined in Scripture, enacted in Israel, refocused in the New Testament community, regulated and guarded by the apostolic fathers, and recovered in the Reformation. It is a worship that can and does still shape the liturgy of many congregations today."--Back cover.
Genesis and the Gospel: the Beginning of Worship -- Worship and Identity: Yahweh and Sabbath in the Torah, Prophets and Gospels -- Worship and Sacred Space: the Grace of Invitation, the Holiness of Boundaries -- The Shape of Biblical Worship -- Worship by the Book -- Worship and Holiness -- Worship in Exile, Synagogues and the Early Church -- Early Patterns for Christian Worship: Clarifying the Faith -- Reformation Patterns for Christian Worship: Recovering the Faith -- Contemporary Patterns for Christian Worship: Keeping the Faith.
Includes bibliographical references (pages 215-219) and index.
Print version record.
Added to collection customer.56279.3
Keywords: Worship in the Bible; Worship -- Biblical teaching; Worship -- History; RELIGION -- Christian Rituals & Practice -- Worship & Liturgy; RELIGION -- Institutions & Organizations; Worship; Worship -- Biblical teaching; Worship in the Bible; Electronic books; History